2003
DOI: 10.1108/09653560310493132
|View full text |Cite
|
Sign up to set email alerts
|

Outlining organisational failure in information systems development

Abstract: Defines the concept of “organisational failure” in information systems (IS) development, and proposes a diagnostic model drawn from research done into IS consultancy firms that develop systems using a variety of methodologies. The research involved a qualitative study aimed at the nature of the development process and the role of organisational issues in this process. The model’s elements and relationships were determined by the research findings. Presents two cases of failure that show how IS failure is roote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Miller (1978) found that living systems can be broken down into a number of smaller subsystems. Yourdon (1989) applied this principle in the development of structured systems methodology in which the often difficult task of successfully developing an information system (Chae and Lanzara, 2006;Guolielmos, 2003), is broken down into developing and implementing smaller, and more easily understood, components of the information system. Successful completion of each component brings the overall information systems development one step closer to its successful completion.…”
Section: General Systems Theory-principlementioning
confidence: 99%
“…Miller (1978) found that living systems can be broken down into a number of smaller subsystems. Yourdon (1989) applied this principle in the development of structured systems methodology in which the often difficult task of successfully developing an information system (Chae and Lanzara, 2006;Guolielmos, 2003), is broken down into developing and implementing smaller, and more easily understood, components of the information system. Successful completion of each component brings the overall information systems development one step closer to its successful completion.…”
Section: General Systems Theory-principlementioning
confidence: 99%
“…This can explain why the projects that have a lot of publicity are more prone to project escalation e.g. Mandata project (Sauer, 2003),Taurus project at London Stock Exchange (Drummond 1996, Goulielmos, 2003, Smith and Keil, 2003, Computer Aided Dispatch system at London Ambulance Service (Finkelstein, 1993, Goulielmos, 2003, and US Census Bureau Information System (Krigsman, 2008).…”
Section: Towards a Model Of Risk Escalationmentioning
confidence: 99%
“…Some researchers have suggested that the values that inform systems engineering, and the methodologies that are used to develop and deploy automation and control systems, require attention, especially in our attempts to understand the dynamics of system failure (Freeman, Stapleton & Byrne (2007), Goulielmos (2005Goulielmos ( ) & (2003). In spite of this, a conceptualisation of culture and organisation has yet to be incorporated into theories of technology design, development and management.…”
Section: Background and Motivationmentioning
confidence: 99%